Maternal fatty acid intake during pregnancy and the development of childhood overweight: a birth cohort study. (5th July 2016) - Hakola, L.; Takkinen, H‐M.; Niinistö, S.; Ahonen, S.; Erlund, I.; Rautanen, J.; Veijola, R.; Ilonen, J.; Toppari, J.; Knip, M.; Virtanen, S. M.; Lehtinen‐Jacks, S.
Summary: Background: Maternal diet during pregnancy may contribute to the risk of offspring adiposity. Objectives: The objective of the study is to explore the associations between maternal antenatal dietary fatty acid intake and the risk of offspring overweight and obesity at the ages of 2 to 7 years. Methods: In a prospective Finnish birth cohort with 3807 mother–child pairs, maternal diet in late pregnancy was assessed with a food frequency questionnaire. Intakes of total fatty acids and individual saturated, monounsaturated and polyunsaturated fatty acids (PUFAs) were calculated. Generalized estimating equation models were used to study the associations of maternal dietary variables with repeatedly measured offspring overweight and obesity. Results: In girls, maternal intake ratio of n ‐6: n ‐3 PUFAs had a U‐shaped association with obesity (adjusted OR for the lowest 2.0 [95% CI 1.27–3.20] and the highest 1.7 [1.03–2.73] vs. the two middle quartiles of n ‐6: n ‐3 PUFAs, p = 0.01). In boys, arachidonic acid (20:4 n ‐6): docosahexaenoic acid + eicosapentaenoic acid ratio was associated with obesity (adjusted OR for the lowest 1.0 [0.60–1.57] and the highest 0.5 [0.26–0.88] vs. the two middle quartiles, p = 0.02). Saturated fatty acids and monounsaturated fatty acids were not associated with overweight or obesity in either sex. Conclusions: Maternal intakes of PUFAs in late pregnancy were associated with risk of later obesity differently in girls and boys.